Objective-Oriented Health Systems Reform - Joseph Kutzin; Susan P. Sparkes; Alexandra J. Earle; Agnes Gatome-Munyua; Nirmala Ravishankar (Health Systems & Reform)
This paper emphasizes the importance of orienting health system reforms to address underlying system-level performance problems. Too often in practice, the objective-orientation that is stressed in health system frameworks gets lost in relation to policies or schemes that are promoted without plausible linkages to the actual objectives of the reforms. The objective-orientation can also get subsumed by political agendas that are disconnected, or can even detract from, people’s health needs. There are three core attributes to objective-oriented health system reform: (i) problem-oriented; (ii) consistent (extent to which reforms are connected to the problems they are meant to address and reflect lessons from global and national experience); and (iii) continuously evaluated. Country experiences reviewed in the paper, and presented in this special issue, illustrate how taking an objective-orientation led reformers to alter the details of implementation. Continuous learning also informed adaptations needed to strategically sequence and link reforms with objectives. An objective-oriented approach enables reformers to: (i) seize windows of opportunity; (ii) find room to maneuver under the label of the reform; (iii) integrate applied research into reform implementation; and (iv) skillfully interpret political statements to align with technical best practices. The approach and attributes laid out in this paper put forward considerations for policy makers as they design, implement, evaluate, and adapt policies to feasibly improve health system performance. They also, importantly, help guard against a rush toward policies or schemes that may sound good in speeches or declarations but do not have a plausible link to objectives.